2014
DOI: 10.1590/s0102-86502014000600007
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological features of esophageal cancer. Squamous cell carcinoma versus adenocarcinoma

Abstract: PURPOSE:To analyze the epidemiological features of patients with esophageal cancer according to the histopathological types: squamous cell carcinoma or adenocarcinoma. METHODS:A total of 100 patients with esophageal cancer, being 50 squamous cell carcinomas and 50 adenocarcinomas were analyzed for demographics, nutritional factors, lifestyle habits, benign pathological conditions associated, like Barrett's esophagus and megaesophagus, tumor stage and survival rates. The nutritional factors evaluated included b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 22 publications
(35 reference statements)
0
36
1
1
Order By: Relevance
“…It has been indicated that the development of esophageal cancer is frequently induced by chronic exposure to irritants, spices, hot drinks, alcohol, and smoking. The risk factors for esophageal squamous cell carcinoma differ from those of esophageal adenocarcinoma [27]. The risk factors for the adenocarcinomas mainly include obesity, gastroesophageal reflux disease and some dietary factors, such as diets high in total fat, saturated fat and cholesterol [28,29], while tobacco smoking and alcohol consumption are the most important risk factors for squamous cell carcinoma [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…It has been indicated that the development of esophageal cancer is frequently induced by chronic exposure to irritants, spices, hot drinks, alcohol, and smoking. The risk factors for esophageal squamous cell carcinoma differ from those of esophageal adenocarcinoma [27]. The risk factors for the adenocarcinomas mainly include obesity, gastroesophageal reflux disease and some dietary factors, such as diets high in total fat, saturated fat and cholesterol [28,29], while tobacco smoking and alcohol consumption are the most important risk factors for squamous cell carcinoma [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal cancer has two predominant histopathological subtypes: esophageal squamous cell carcinoma (ESCC) and esophageal adenocarcinoma (EAC). The risk factors and genomic characteristics of each of these cancers are quite different . Most studies show that the risk of EAC is inversely associated with adult height, but the associations between ESCC risk and adult height are erratic .…”
Section: Introductionmentioning
confidence: 99%
“…There are two histological types of esophageal cancer: Squamous cell carcinoma (SCC) and adenocarcinoma (ADE) (2). Although the incidence of ADE has increased rapidly in Western countries during the last 30 years, SCC is still the major type of esophageal cancer-related threat in Asia, Southern and Eastern Africa, and Northern France (3).…”
Section: Introductionmentioning
confidence: 99%